CAUSALITY BETWEEN PUBLIC DEBT, PUBLIC DEBT SERVICE AND ECONOMIC GROWTH IN AN EMERGING ECONOMY - SAUNGWEME, Talknice; ODHIAMBO, Nicholas M. (Studia Universitatis Babeș-Bolyai Oeconomica, 2020)
This paper explores the causality between public debt, public debt service and economic growth in South Africa covering the period 1970 – 2017. The study employs the autoregressive distributed lag (ARDL) bounds testing approach to cointegration and the multivariate Granger-causality test. The empirical results indicate that there is unidirectional causality from economic growth to public debt, but only in the short run. However, the study fails to establish any causality between public debt service and economic growth, both in the short run and long run. In line with the empirical evidence, the study concludes that it is economic growth that drives public debt in South Africa, and that the causal relationship between public debt and economic growth is sensitive to the timeframe considered. The paper recommends policymakers in South Africa to consider growth-enhancing policies in the short run, since poor economic performances may lead to high public debt levels. JEL Classification: H63, O47